Degenerative Lumbosacral Syndrome in Dogs – surgical management strategies and new insights on outcome - Gomes, Sérgio Luís A C R (2022)
Degenerative Lumbosacral Stenosis (DLSS) is a common debilitating condition affecting dogs, describing a multifactorial syndrome arising from the compression of the cauda equina and its associated nerve roots. Typically, cases present following a protracted history of suspected lumbar pain, persistent or episodic, made evident in activities where more force is loaded at the lumbosacral joint and its associated neuroforamina. Active, working, military or agility dogs are thought to be at risk of developing DLSS. Diagnosis of DLSS relies on a compatible clinical history, exclusion of conditions with similar presentation and evidence of cauda equina compromise on diagnostic imaging. Cross-sectional imaging and particularly MRI are necessary to reach a DLSS diagnosis. A protracted, persistent or episodic history of lumbar pain, difficulties jumping and pelvic limb lameness, in the absence of overt orthopaedic disease, should alert the clinician that DLSS is possible. Foraminal stenosis has been increasingly recognised as part of the DLSS syndrome, however previous to this thesis, decompressive surgery in clinically affected dogs had only been reported in a single study. Furthermore, alternative treatments to surgery in canine degenerative lumbosacral stenosis (DLSS) remain limited and reliable predictors of outcome are lacking. This considered, this thesis aimed to: (1) review retrospectively the short and long-term outcome in a cohort of canine patients who underwent lateral foraminotomy in the treatment of lumbosacral foraminal stenosis, (2) assess the usefulness of a single epidural steroid injection (ESI) in the management of DLSS, (3) evaluate ESI as a predictor of outcome following decompressive surgery and (4) compare the outcomes of ESI and decompressive surgery. A set of hypotheses were proposed: (1) lateral foraminotomy would be a safe and useful treatment in cases of lumbosacral foraminal stenosis, (2) ESI can be effective in DLSS cases, leading to transient alleviation of clinical signs, (3) ESI can be a reliable predictor of surgical outcome, e.g. a positive response to ESI can indicate a positive response to surgical decompression, (4) surgical decompression can lead to a more favourable outcome than a single ESI. In order to address these questions two studies, one retrospective and one prospective were developed. For the first study, clinical records were reviewed retrospectively from 45 dogs which had undergone lateral foraminotomy at the lumbosacral junction either alone or in combination with decompressive midline dorsal laminectomy. For the second study, dogs diagnosed with DLSS were prospectively recruited and administered an epidural steroid injection (ESI). If clinical signs persisted or relapsed, decompressive surgery was recommended. Follow-up was obtained. Forty-five dogs were included in the retrospective study shown that short-term outcome at six weeks was assessed by the surgeon to be good (11.1 per cent) or excellent (88.9 per cent) in all 45 cases. Long-term outcome beyond six months for lumbosacral syndrome was assessed by the owner as excellent in all 34 cases for which follow-up was available despite recurrence in five cases. Recurrence of clinical signs was not related to re-establishment of foraminal compression at the surgical site when assessed on repeat MRI and was managed by either contralateral foraminotomy in one case or conservative management with excellent response. Thirty-two dogs were recruited for the prospective study that underwent ESI, with seventeen having subsequent surgery. Improvement after ESI was seen in 27/32 dogs (84.4%), with 17/22 (77.2%) relapsing within 6 months. Five dogs failed to respond to ESI and another five dogs (15.6%) presented a persistent post-ESI favourable response (mean follow-up time, 9.4 months). Post-surgical improvement was identified in all dogs. Outcome was favourable following surgical decompression, with a statistically significant difference towards reduced pain, increased mobility, and a greater quality of life score. This study was not able to demonstrate that ESI could predict surgical outcome.